Research methodology : Tools, methods & techniques - Sundram, Veera Pandiyan Kaliani; Rajagopal, Premkumar; Bahrin, Atikah Shamsul (Malaysia Logistics and Supply Chain Association, 2016)
This book provides the basic information about research methodology such as: introduction to bussiness research, research problem, research question and research objective, literature review, framework and hypotheses development, research design, measurement and scale, sampling, questionaire, data collection, quantitative and qualitative data analysis, and research report.